Key Aggregate Cryptography in Cloud for Scalable Data Sharing - Sonali A, Karale; Sachin D, Choudhari (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing provide facilitates computing assets on demand by the use of service provider. In IT communications cloud computing is out sourcing by the use of the Internet and maintaining own hardware and software environment. It is there whenever you need it, as much as you need, and you pay as you go and only for what you use. Security is a prim concern in the use of cloud computing. In this paper, we have presented encryption based security algorithms for cloud computing. Data Sharing is an important functionality in cloud storage. We show how to securely share data. We describe new public key cryptosystems which produce constant size cipher text but the other encrypted files outside the set remain confidential.